Pelatihan Pembuatan Kreasi dari Barang Bekasdi SMP dan SMA YPPKK Moria Kota Sorong - Maya Pattiwael; Amatus Turot; Adriana Syufi; Seppy Pigome; Yance Majiwi; Burmanus Alfons; Melvin Kalagison; Risna Masauna (CV. ITTC INDONESIA, 2025)
YPPKK Moria Junior and Senior High Schools in Sorong City are examples of schools that are always open and welcoming to activities that can broaden their students' knowledge. This demonstrates the school's commitment to developing character and environmental awareness in its students. The method used is participatory and educational, encompassing several stages: preparation, outreach and education, training, and evaluation. The material presented at the beginning of the activity aimed to broaden participants' understanding of the importance of reusing used goods. The training resulted in three creations made from used goods: a cardboard piggy bank, a calendar paper bag, and a pencil case made from cigarette cans. The activity went well, as evidenced by the participants' enthusiasm in creating their creations. Their commitment from start to finish demonstrates their strong desire to create. As a follow-up to this activity, the school needs to provide mentoring to students who want to enhance their creativity, focusing on managing used goods.